(untitled) (Journal of Population and Development, 2022)
Rape and sexual violence is a deep-rooted issue in Nepal, as it is around the world. The number of reported rape cases continues to rise despite strict laws in Nepal. The topic is framed as part of women issue of gender based violence. This article tries to highlight the trend and situation of sexual assault (rape) analyzing the existing rape cases. The study is based on descriptive as well as analytical in nature. Sources of information in this study are secondary data like published and un- published research papers, journal articles and survey reports with desk review method. Although most countries have laws prohibiting sexual assault and violence. While the number of rape cases and sexual violence has increased in several nations in recent years, there are still countries where no rape incidents have been documented. The Nepal Police in 2021 reported that up to seven women and girls are raped every day in the country, most of them by neighbors, relatives and acquaintances. Therefore, the state should not fail to protect the rights of the victims.” The incidents of murder and murder after rape have increased drastically in the recent times. According to statistics, 17 women were murdered after rape in the past four years. One point that has come under intense scrutiny is that law in Nepal specifies women and girls as the victim in case of rape. Despite the Constitution and law guarantees, instances of rape are increasing in Nepal. In the other, sexual violence by intimate partner is largely unreported due to social stigma as well as the belief that forced sexual relation by a husband without the consent of the wife doesn’t constitute violence. Many cases of rape and sexual violence go unreported to police because of social stigma, lack of trust in the justice system and lack of protection of victims.